(untitled) (LACCEI, 2024)
Today, market conditions have forced insurance companies to adapt strategic digital marketing actions, thus creating a better two-way communication channel that improves interconnection with users, obtaining adequate brand and service recognition and positioning. Based on this perspective, the objective of this text is to determine how commercial companies in the insurance sector use digital networks as a means of communication with their users, with the aim of establishing actions that improve their competitive capacity in the market. The methodology used was based on the variables of participation in digital social profiles, for which an observation instrument was developed consisting of six variables referring to the 4Cs of marketing and the variety of content and these five digital networks were analyzed: Facebook, Instagram , YouTube, Twitter, LinkedIn. The results indicated that some of the digital networks that companies in the insurance sector maintain and feed do not disclose adequate content, therefore, users and consumers do not perceive the publication of updated information, which demonstrates a waste in the use of technologies. of the information. allow a strengthening of the "corporate" digital identity among users, to gain greater credibility and trust on their part.